First detection of Mycobacterium ulcerans DNA in environmental samples from South America. - Aaron Morris; Rodolphe Gozlan; Estelle Marion; Laurent Marsollier; Demetra Andreou; Daniel Sanhueza; Rolland Ruffine; Pierre Couppié; Jean-François Guégan (Public Library of Science (PLoS), 2014)
The occurrences of many environmentally-persistent and zoonotic infections are driven by ecosystem changes, which in turn are underpinned by land-use modifications that alter the governance of pathogen, biodiversity and human interactions. Our current understanding of these ecological changes on disease emergence however remains limited. Buruli ulcer is an emerging human skin disease caused by the mycobacterium, Mycobacterium ulcerans, for which the exact route of infection remains unclear. It can have a devastating impact on its human host, causing extensive necrosis of the skin and underlying tissue, often leading to permanent disability. The mycobacterium is associated with tropical aquatic environments and incidences of the disease are significantly higher on floodplains and where there is an increase of human aquatic activities. Although the disease has been previously diagnosed in South America, until now the presence of M. ulcerans DNA in the wild has only been identified in Australia where there have been significant outbreaks and in western and central regions of Africa where the disease is persistent. Here for the first time, we have identified the presence of the aetiological agent's DNA in environmental samples from South America. The DNA was positively identified using Real-time Polymerase Chain Reaction (PCR) on 163 environmental samples, taken from 23 freshwater bodies in French Guiana (Southern America), using primers for both IS2404 and for the ketoreductase-B domain of the M. ulcerans mycolactone polyketide synthase genes (KR). Five samples out of 163 were positive for both primers from three different water bodies. A further nine sites had low levels of IS2404 close to a standard CT of 35 and could potentially harbour M. ulcerans. The majority of our positive samples (8/14) came from filtered water. These results also reveal the Sinnamary River as a potential source of infection to humans.